SAFETY OF INFORMATION AND COMMUNICATION SYSTEMS. QUESTIONS OF TERMINOLOGY AND BASIC DEFINITIONS - Юдін, О. (Science-based technologies, 2012)
The article analyzes the regulatory provision and describes the basic questions of terminology' and definitions of information security. Studied history and legal steps to create a regulatory framework of information technology and security.